2017
DOI: 10.3354/dao03099
|View full text |Cite
|
Sign up to set email alerts
|

First report of Rahnella aquatilis infection in crucian carp Carassius auratus in China

Abstract: Rahnella aquatilis infection is rare in aquaculture. Here, a Gram-negative rod-shaped bacterium was isolated from diseased crucian carp Carassius auratus in Xuzhou City, Jiangsu Province, eastern China. The isolate was tentatively named strain KCL-5, and subsequently identified as R. aquatilis by biochemical properties and molecular techniques. The results showed that the isolate KCL-5 was most closely related to the type strain ATCC33071 (= DSM4594) of R. aquatilis, which shared 99.67, 96.26 and 99.58% nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…The relative abundance of Elizabethkingia was higher in the control group than in the other groups and the gentamicin bath did not have an inhibitory effect. Elizabethkingia is pathogenic and has four known species, including Elizabethkingia miricola, which caused a multi-regional outbreak of meningitis-like cases in a Chinese black spotted frog farm in (Hu et al, 2017. Elizabethkingia was not sensitive to gentamicin in this study.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The relative abundance of Elizabethkingia was higher in the control group than in the other groups and the gentamicin bath did not have an inhibitory effect. Elizabethkingia is pathogenic and has four known species, including Elizabethkingia miricola, which caused a multi-regional outbreak of meningitis-like cases in a Chinese black spotted frog farm in (Hu et al, 2017. Elizabethkingia was not sensitive to gentamicin in this study.…”
Section: Discussionmentioning
confidence: 68%
“…Studies have shown that gentamicin is effective for serious gram-negative bacterial infections (Wiedenhoft, Hayashi & Coffin, 2017). Pathogenic bacteria, such as Arcobacter butzleri (Rathlavath et al, 2017), Staphylococcus aureus (Awad et al, 2017), Pseudomonas aeruginosa (Lamari, Chakroun & Rtimi, 2017), Acinetobacter (Jie et al, 2017) and Rahnella aquatilis (Lü et al, 2017), which cause diseases in aquatic animals, are all sensitive to gentamicin. Flavobacterium psychrophilum is a serious pathogen of salmonids.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence identity to other bacterial organisms was significantly lower, at 98% and below and mainly to Hafnia and Serratia species. While Hafnia and Serratia species are commonly isolated from finfish, sometimes being involved in opportunistic infections, reports of isolation of Rahnella and Rouxiella species mainly consist of R. aquatilis 38 . Although presence of opportunistic agents (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The gram staining test was conducted by the Hucker method, and the morphological characteristics of three colonies were observed under a microscope prior to physiological and biochemical testing (Lü et al. 2017). Physiological and biochemical tests for isolate KCP‐516 were performed using a commercial microbacteria biochemical test system (Tianhe, Tianjin, China), including gelatinase (enzyme number 3.4.24.24; IUBMB 1992), oxidase (1.9.3.1), phenylalanine, citrate (Simmons), tartrate, malonate, gluconate, starch, glucose, galactose, mannose, xylose, fructose, sorbitol, mannitol, and inositol, among others.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR products were purified using a QIAquick PCR Purification Kit (Qiagen, Valencia, California) and cloned into pMD18‐T vector (Takara, Tokyo, Japan) to transform Escherichia coli DH5α competent cells (Lü et al. 2017). The positive clones were sequenced in both directions by Genewiz.…”
Section: Methodsmentioning
confidence: 99%